International symposium innovative applications of shells and spatial forms / International Association for Shell and Spatial Structures: Oxford & IBH Pub 624.1776 In65 V-3
International symposium innovative applications of shells and spatial forms / International Association for Shell and Spatial Structures: Oxford & IBH Pub 624.1776 In65 V-3 No. of Copies : 1